The relationship between uric acid and total femur bone mineral density in hypertensive and non-hypertensive populations - Yingjie Su; Yingjie Su; Yingjie Su; Ning Ding; Ning Ding; Ning Ding; Yang Zhou; Yang Zhou; Yang Zhou; Guifang Yang; Guifang Yang; Guifang Yang; et al. (Frontiers in Endocrinology, 2022)
ObjectiveThis study aimed to explore the association between uric acid (UA) and total femur bone mineral density (BMD) in hypertensive and non-hypertensive groups.MethodsWe conducted a cross-sectional study of 13,108 participants in the NHANES database, including 4,679 hypertensive and 8,429 non-hypertensive subjects. A weighted multiple linear regression analysis was conducted to explore the association between UA and total femur BMD.ResultsIn the hypertensive group, the relationship between UA and total femur BMD was positive [β, 3.02 (95% CI, -0.44 to 6.48), p = 0.0962). In the non-hypertensive group, the association was significantly positive [β, 5.64 (95% CI, 2.06–9.22), p = 0.0038]. In gender-stratified analysis, UA was analyzed as a continuous variable and a categorical variable (quartile). The significantly positive association was present in both the hypertensive male group [β, 5.10 (95% CI, 0.98–9.21), p for trend = 0.0042] and non-hypertensive male group [β, 10.63 (95% CI, 6.32–14.94), p for trend = 0.0001]. A smooth curve fitting showed that in the hypertensive male group, the relationship between UA and total femur BMD was an inverted U-shaped curve. In the hypertensive female group, the relationship was basically negative. In the non-hypertensive population, the relationship between UA and total femur BMD was an inverted U curve in both men and women.ConclusionIn the hypertensive male group, the association between UA and total femur BMD was an inverted U-shaped curve. As to women, the relationship was basically negative. In the non-hypertensive group, the association between UA and total femur BMD was an inverted U-shaped curve in different genders.